THE URGENCY OF COUNSELING AS AN ADDITIONAL CRIMINAL SANCTION TO PREVENT DIVORCE IN THE PERSPECTIVE OF ISLAMIC FAMILY LAW - Armasito Armasito; Yuli Kasmarani (Ta'zir)
Domestic violence (marietal crime) in Indonesia often occurs and there is always an increase, domestic violence is one of the factors causing the high divorce rate in Indonesia. In the PKDRT Law, the regulation of criminal sanctions of imprisonment or confinement is not also effective as an ultimum remedium. On the other hand, judges are more inclined to use the sanction of imprisonment without considering counseling as an additional criminal which is an applicable policy that needs to be tried in maintaining harmony and integrity of marriage. For this reason, it is necessary to study the urgency of counseling as an additional criminal sanction for domestic violence crimes and how Islamic family law assesses this. This research is a normative research with a normative juridical approach that uses study materials in the form of Law Number 23 of 2004 concerning the Elimination of Domestic Violence, the Quran, hadith, and books and articles related to the problem studied. Then the study material is analyzed in a qualitative descriptive manner. The results of the study show that domestic violence has a very significant impact on victims, ranging from suicide attempts, physical injuries, being infected with sexually transmitted diseases, paralysis, mental health disorders, loss of confidence, job loss, criminalization, to divorce. So, additional counseling for domestic violence perpetrators should be applied to prevent bad things from happening, one of which is divorce. The existence of additional counseling provides a more controlled space and process for domestic violence perpetrators to improve themselves, domestic violence victims can recover from trauma, and avoid wider impacts in marriage (divorce). In Islamic Family Law, maintaining the integrity of the family is paramount and avoiding things that can cause divorce. Therefore, additional counseling needs to be imposed as part of maqoshid al-Ghayatu li al-nikahi ila ahli al-sakinah wa al-waRahmah